Big data technology in shari’ah compliance risk management (SCRM): a view of information technology in Islamic finance risk management - Ridhwan, Muhammad Saiful; Khairuddin, Nur Dini; Suhaimi, Mohd Adam (International Association of Islamic Banks, 2014)
The global Islamic finance sector is booming and is likely to sustain a stable growth. With many Islamic Finance products introduced over the years, the demand in studying risk pertaining to Islamic finance product is becoming a major concern. The main reason to manage risk is to attain the organizations’ objectives on financial stability. In Islamic finance the risk is much further than just financial itself because we have to look into activities related to the Islamic Finance existence. These activities related to Islamic Finance must abide by the Shari’ah law. Thus, the Shari’ah non-compliance is a unique risk for Islamic finance which needs a special risk management apart from typical risk management of conventional finance. From Information Technology point of view this problem can be addressed by implementing Big Data technology in risk management systems. This will enable financial bodies to identify the breach of Shari’ah law in the Islamic Finance activities. Big Data technology have the ability to perform analysis of vast amounts of information that can be converted into decision making and priority of impact level in risk event. Adopting Big Data technology in risk management, opens a new door to Financial Risk Management techniques with primarily focuses on Islamic finance.